Corrective Osteotomies of Phalangeal and Metacarpal Malunions Using Patient-Specific Guides: CT-Based Evaluation of the Reduction Accuracy. (November 2018) - Hirsiger, Stefanie; Schweizer, Andreas; Miyake, Junichi; Nagy, Ladislav; Fürnstahl, Philipp
Background: Surgical planning of corrective osteotomies is traditionally based on conventional radiographs and clinical findings. In the past 10 years, 3-dimensional (3D) preoperative planning approaches with patient-specific guides have been developed. However, the application of this technology to posttraumatic deformities of the metacarpals and phalangeal bones has not yet been investigated. Our goal was to evaluate the feasibility of the surgical application to the latter and to evaluate the extent and precision of correction.Methods: We present results of 6 patients (8 osteotomies) treated with phalangeal or metacarpal corrective osteotomy. Deformities were located in the third ray in 1, fourth ray in 3, and fifth ray in 4 cases. Six malunited metacarpal bones (1 intra-articular) and 2 deformed proximal phalanges were treated. Computer-based 3D preoperative planning using the contralateral hand as a template allowed the production of 3D-printed patient-specific guides that were used intraoperatively for navigation. The precision of the reduction was assessed using pre- and postoperative computed tomography by comparing the postoperative bone model with the preoperatively simulated osteotomy. Range of motion and grip strength were documented pre- and postoperatively.Results: The mean follow-up time was 6 months (range: 5-11 months). Rotational deformity was reduced from a mean of 10.0° (range: 7.2°-19.3°) preoperatively to 2.3° (range: 0.7°-3.7°) postoperatively, and translational incongruency decreased from a mean of 1.4 mm (range: 0.7-2.8 mm) to 0.4 mm (range: 0.1-0.9 mm).Conclusion: Preliminary results indicate that a precise reduction for corrective osteotomies of metacarpal and phalangeal bones can be achieved by using 3D planning and patient-specific guides.